Plasma micrornas as a biomarker for detection of colorectal cancer in Hospital Universiti Sains Malaysia - Mohamed, Syarah Syamimi (2023)
Colorectal cancer (CRC) is one of the cancer with a low survival rate and usually end with death. Colonoscopy is currently the gold standard in detecting CRC disease. However, due to the inconvenience of the procedure, it becomes less appealing. Since its discovery, microRNA (miRNA) has pioneered a new era of molecular diagnosis. MiRNA is a short post-transcriptional regulatory that targets messenger RNA (mRNA), either causing degradation or altering the protein translation. MiRNA expression is dysregulated in CRC tissue. The presence of miRNAs in plasma is thought to provide non-invasive screening tools for detecting disease and may aid early detection. Even though many miRNAs have been profiled in CRC, there is still ambiguity on the robustness of the reported miRNAs in detecting CRC. Thus, a miRNA expression study was conducted using a population sample in Hospital Universiti Sains Malaysia to search for potential circulating miRNAs as CRC screening biomarkers. The significant miRNA profile in CRC tissue was obtained by comparing their expression to its adjacent normal tissue. A few upregulated miRNAs from tissue (hsa-miR-20a-5p, hsa-miR-21-5p, and hsa-miR-210-3p) were validated in their plasma and other independent study groups (CRC and healthy individuals). Relatively, among these three miRNAs, hsa-miR-21-5p (FC=3.87) has the highest fold change (FC) in the plasma of CRC patients compared to healthy individuals, followed by hsa-miR-20a-5p (FC=1.23) and hsa-miR-210-3p (FC=-0.21). However, expression of hsa-miR-210-3p in plasma was inconsistent as compared to tissue. According to Spearman correlation analysis, hsa-miR-21-5p has a strong positive correlation (r=0.84) compared to hsa-miR-20a-5p (r=0.20). Meanwhile, hsa-miR-210-3p showed a negative correlation (r=-0.75) between tissue and plasma. Lastly, we evaluated the diagnostic performance of individual and combined miRNAs using receiver operating characteristics curve analysis according to stages. Our studies revealed that hsa-miR- 20a-5p (AUC: 0.82, 86% sensitivity and 88% specificity) potentially act as a biomarker panel for early CRC, whereas both hsa-miR-21-5p and hsa-miR-210-3p (AUC: 1.0, 100% sensitivity and specificity simultaneously) are for advanced CRC. Combining all three miRNAs also gives good discriminative power (AUC:0.98) between CRC patients and healthy individuals with 96% sensitivity and 75% specificity. Meanwhile, the combination of two miRNAs, namely hsa-miR-21-5p and hsa-miR-210-3p, and hsa-miR-20a-5p and hsa-miR-21-5p, resulting in discrimination power of 0.97 and 0.91, respectively. The study discovered three circulating miRNAs, hsa-20a-5p, hsa-miR-21-5p, and hsa-210-3p, which may be minimally invasive diagnostic biomarkers. Hsa-miR-21-5p and hsa-miR-210-3p have strong positive and negative correlations with their tissue counterparts. In conclusion, individual hsa-miR- 21-5p has the highest discriminative power, while combined miRNAs showed that combining all three was the best combination with the highest discriminatory power.